Sarah Anne Jane Locke Smith and husband William Thomas Smith and their children. - Unknown:::Creator::::::::::::
Sarah Locke Smith with her husband William T. Smith and their children. Sarah Locke Smith is holding her infant daughter, Gertrude and she is sitting with her husband and Ethel on a garden bench. Her other daughter, Mildred is standing. Her boys Harry, Elmer and Warren (from left to right) are also standing behind their parents.